2004
DOI: 10.1115/1.1710867
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Assessing Vehicle Interior Design Ergonomics in a Virtual Environment

Abstract: The predictive value and the reliability of evaluations made in immersive projection environments are limited when compared to the real world. As in other applications of numerical simulations, the acceptance of such techniques does not only depend on the stability of the methods, but also on the quality and credibility of the results obtained. In this paper, we investigate the predictive value of virtual reality and virtual environments when used for engineering assessment tasks. We examine the ergonomics eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Dynamic, fixed-based simulators have been found to have good relative validity for lane keeping in driving tasks (Reed and Green, 1999). VR has been reported as a suitable tool for evaluating design alternatives (Lawson and Burnett, In press); it is often considered to give greater relative validity than absolute validity (Reuding and Meil, 2004;Naghiyev and Sharples, in press). Eye tracking (and lane deviation) are standard measures of driver distraction (e.g.…”
Section: Studying Driver Distractionmentioning
confidence: 99%
“…Dynamic, fixed-based simulators have been found to have good relative validity for lane keeping in driving tasks (Reed and Green, 1999). VR has been reported as a suitable tool for evaluating design alternatives (Lawson and Burnett, In press); it is often considered to give greater relative validity than absolute validity (Reuding and Meil, 2004;Naghiyev and Sharples, in press). Eye tracking (and lane deviation) are standard measures of driver distraction (e.g.…”
Section: Studying Driver Distractionmentioning
confidence: 99%
“…Virtual environments have progressed and are being used for conceptual layouts. They are, however, insufficient for more refined ergonomics assessments [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to depth perception issues, this conflict can lead to visual discomfort or simulator sickness (Chen et al, 2014;Häkkinen et al, 2006;IJsselsteijn et al, 2000). The use of CAVEs has been analysed in a number of applications including driving simulators (Kim et al, 2005;Mollenhauer et al, 2005) and other aspects of automotive ergonomics including reach and visibility (Reuding & Meil, 2004). Reuding and Meil (2004) conducted a study to investigate the reliability of the CAVE for in-vehicle reach and visual task performance by comparing data against those obtained from a physical buck.…”
Section: Introductionmentioning
confidence: 99%
“…The use of CAVEs has been analysed in a number of applications including driving simulators (Kim et al, 2005;Mollenhauer et al, 2005) and other aspects of automotive ergonomics including reach and visibility (Reuding & Meil, 2004). Reuding and Meil (2004) conducted a study to investigate the reliability of the CAVE for in-vehicle reach and visual task performance by comparing data against those obtained from a physical buck. They concluded that to obtain reliable results the CAVE must be used as a comparative tool, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation